Variable presentation of anaplastic large‐cell lymphoma in patients with breast implants. Issue 10 (1st April 2015) - Locke, Michelle B.; Lofts, Julian
Abstract: Background: Anaplastic large‐cell lymphoma (ALCL) has recently been reported in women with breast implants. The incidence of breast implant‐related ALCL is extremely rare and most surgeons would not expect to see this disease in their career. However, the senior author has had three women present to his practice with ALCL over a 2‐year period. Methods: The three patients and their presentation were reviewed to establish the presenting complaint in each case of subsequently diagnosed ALCL. Literature was reviewed to establish appropriate treatment protocols for any subsequent patients. Results: The average time between first implant placement and presentation with breast implant‐associated ALCL was 13.3 years (range: 10–16 years) and age at presentation was 49 years (range: 45–53 years). Each presentation was somewhat different, being a palpable mass, a painless seroma and a painful seroma. Both patients with seroma underwent ultrasound‐guided aspiration of fluid which confirmed ALCL. All patients underwent implant removal and complete capsulectomy. The patient with a mass at presentation initially declined adjuvant treatment but subsequently developed an ALCL‐associated seroma and was treated with surgery and post‐operative chemotherapy. Conclusion: Patients with breast implant‐associated ALCL can present with different clinical signs and symptoms. Late seroma is a relatively common presentation of breast implant‐associated ALCL. While firm guidelines for the management of breast implant‐related ALCL are lacking, we suggest that any late seroma in the absence of infection should be managed with aspiration and cytological analysis of the fluid.